Ascertaining trust of information transmitted during a disaster - Yusoff, Y. (Universiti Teknikal Malaysia Melaka, 2016)
During a disaster, especially at the beginning, a huge amount of information is being communicated by the victims to the authority/rescuer. With the presence of ICT applications and smartphone devices, the communications can be carried out easily. However, these ease of communication created one critical issue that is the reliability of the transmitted information. One of the potential solutions is to use trust algorithm to identify the trusted information. The trust engine can help to filter and verify the reliability and validity of the transmitted information. With the ability to identify trusted information, the authority and rescuer would be able to channel and prioritize their rescue efforts to the more critical disaster areas. A prototype, running on Android platform and Web server, was developed to demonstrate the proposed solution.